HAPLOSTIGMA BALDISII SP. NOV. (LYCOPHYTA) DEL DEVÓNICO DE LA PRECORDILLERA DE SAN JUAN, ARGENTINA (Ameghiniana, 2014)
Casts and moulds of a small Iycophyte, Haplostigma baldisii sp. nov., are described and figured. They occur in Devonian shales of the Chigua Formation, sierra del Volcán, San Juan Province. The plants were herbaceous, unbranched, bearing closely spaced simple, short enations, forming wide rows, closely spaced, altemate, with sigillarioid disposition (orthostichies). Enations exhibit subhexagonal bases of subcircular to transversely oval section and blunt to acute apex. Cornments are made on the validity of the genus name Haplostigma Seward. The new species is compared to Devonian and Carboniferous species from Africa and Argentina.